Breaking the Upper Limit of Substitution Concentration in Li Argyrodite Solid Electrolytes Using a Single-Solvent-Mediated Approach - Choi, Ji Woong; Kim, Woong-Ju; Hwang, Suk-Ho; Kim, Sung-Chul; Shin, Yoonju; Ahn, Sangdoo; Lee, Young Joo; Kang, Jin Gu; Kim, Dong-Wan (Wiley-VCH Verlag, 2025)
Although raising the substitution concentration of aliovalent cations in Li argyrodite solid electrolytes could boost solid-state battery performance, surpassing the known substitution limit has not been attempted. In this study, the upper substitution limit of a Li6+xP1-xSixS5Br solid electrolyte is increased using a single-solvent-mediated approach. The limit attained through this method is approximate to 40%, whereas that achieved through solid-state ball milling is approximate to 30%. This result is validated by monitoring variations in the interplanar distance, Raman shift, and ionic conductivity with respect to the substitution level. The ionic conductivity of Li6.4P0.6Si0.4S5Br is as high as approximate to 3.1 mS cm-1, exceeding that accomplished through ball milling. The enhanced limit is ascribed to the reduced particle size, which leads to an increased surface-area-to-volume ratio of the particles. This interpretation is supported by a theoretical formalism developed based on substituent accumulation within the space-charge layers, which predicts how the technical limit depends on the surface-volume fraction. A Li// Li6.4P0.6Si0.4S5Br//Li symmetric cell demonstrates excellent Li plating and stripping over extended cycling. A full cell incorporating Li6.4P0.6Si0.4S5Br retains approximate to 67% (96 mAh g-1) of its initial capacity (143 mAh g-1) after 50 cycles at 0.2 C, and delivers 76 mAh g-1 at 1 C.